Islamic Communication in Improving the Religiosity of Migrant Children in Sentul Guidance Center Malaysia - Kholilurrohman, Kholilurrohman (Jurnal Ilmiah Syi'ar, 2024)
Islamic communication is one of the keys in improving the religiosity of migrant children in Sentul Guidance Center Malaysia, with the aim of informing, changing attitudes, opinions or behavior of someone either verbally or indirectly, to be able to communicate well, it is required not only to understand the process, but also to be able to apply knowledge creatively. This article aims to explore Islamic communication in Sentul Guidance Center Malaysia in enhancing the religiosity of migrant children. The research method is qualitative with a case study approach. Research data were obtained through observation and interviews. The data is then analyzed, compiled, and presented in the form of a report or narrative. The results of this study show: First, Sentul Guidance Center implements qaulan sadidan when practicing congregational prayer with migrant children. Second, Sentul Guidance Center implements qaulan baligha, to migrant children to care about the environment. Third, Sentul Guidance Center implements qaulan ma'rufa when inviting migrant children to live a healthy life by exercising. Fourth, Sentul Guidance Center implements qaulan karima when practicing duha prayer with migrant children. Fifth, Sentul Guidance Center implements qaulan layyina when habituating reading surahs in every learning process with migrant children. Sixth, Sentul Guidance Center implements qaulan maysura, when inviting Malaysian migrant children to behave in a disciplined manner.